Resin composite characterizations following a simplified protocol of accelerated aging as a function of the expiration date - Perlatti D'Alpino, Paulo Henrique; Goncalves Vismara, Marcus Vinicius [UNESP]; Medeiros Mello, Luciano Marcelo de; Di Hipolito, Vinicius; Miranda Gonzalez, Alejandra Hortencia; Oliveira Graeff, Carlos Frederico de [UNESP] (Elsevier B.V., 2014)
This study evaluated the mechanical, thermal, and morphological characteristics of different classifications of dental composites as a function of the material condition (new, aged and expired). Specimens were obtained according to these factors: Composites: Filtek P60, Filtek Z250, Filtek Z350XT, and Filtek Silorane; and Material conditions: new, aged, and expired. The syringe composites underwent an accelerated aging protocol (Arrhenius model). The flexural strength (FS) and flexural modulus (E) were obtained. The thermogravimetric analysis (TGA) and differential thermal analysis (DTA) were also performed and the glass transition temperature (T-g) and the weight loss calculated. Topographic analysis of the composites was performed under SEM. The material conditions influenced the mechanical properties of the composites. The silorane composite exhibited a characteristic thermal behavior different from that of the methacrylates. In general, the T-g increased after the accelerated aging protocol and decreased for expired ones, compared to the new composites. A significant increase in FS of Filtek Z350XT after aging was accompanied by an increase in the T-g. The filler packings were in accordance with the manufacture's information. The topographic aspects of the composites were modified as a function of the material condition. The mechanical properties of the composites following a simplified protocol of accelerated aging varied as a function of the expiration date. The silorane composite presented a characteristic thermal behavior. Although the dental manufacturers may not be able to control variables as storage temperature and transportation conditions, these effects on the composite clinical performance can be minimized if properly considered. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Composite resins; Methacrylate; Silorane; Mechanical properties; Thermal analysis; Accelerated aging